PENGUATAN PEMAHAMAN KEAGAMAAN DAN SILATURAHMI BERBASIS GENDER MELALUI MAJELIS TAKLIM MUSLIMAH JAMAAH MASJID JAMI NURUL IMAN - Ahmad Farhan; Agusri Fauzan; Widya Putri; Halimah Nurazizah; Raul Gonzales; Ragil Efryan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Religious strengthening activities through Muslimah Ta'lim assemblies represent one of the most effective grass-roots methods for deepening women's Islamic understanding while simultaneously reinforcing communal bonds (silaturahmi). This study employs a systematic literature review method to analyze the role of gender-based Muslimah Ta'lim in the context of Community Service Activities (KKN) at Jami' Nurul Iman Mosque congregation. Drawing on theories of gender in Islam, social learning, and Islamic community empowerment, this article demonstrates that Muslimah Ta'lim functions not merely as a religious education forum but also as a strategic space for the construction of women's religious identity, the strengthening of gender justice values in the Muslim family and community, and the cultivation of productive silaturahmi networks. The findings underscore the importance of integrating gender-sensitive approaches into the curriculum and facilitation of Ta'lim assemblies, so that women participants not only improve their religious literacy but also develop a deeper awareness of their rights and roles in family and social life.